Cohort profile: the multigeneration Respiratory Health in Northern Europe, Spain and Australia (RHINESSA) cohort. Issue 6 (2nd June 2022) - Svanes, Cecilie; Johannessen, Ane; Bertelsen, Randi Jacobsen; Dharmage, Shyamali; Benediktsdottir, Bryndis; Bråbäck, Lennart; Gislason, Thorarinn; Holm, Mathias; Jõgi, Oskar; Lodge, Caroline J; Malinovschi, Andrei; Martinez-Moratalla, Jesus; et al.
Abstract : Purpose: The Respiratory Health in Northern Europe, Spain and Australia (RHINESSA) cohort was established to (1) investigate how exposures before conception and in previous generations influence health and disease, particularly allergies and respiratory health, (2) identify susceptible time windows and (3) explore underlying mechanisms. The ultimate aim is to facilitate efficient intervention strategies targeting multiple generations. Participants: RHINESSA includes study participants of multiple generations from ten study centres in Norway (1), Denmark (1), Sweden (3), Iceland (1), Estonia (1), Spain (2) and Australia (1). The RHINESSA core cohort, adult offspring generation 3 (G3), was first investigated in 2014–17 in a questionnaire study (N=8818, age 18–53 years) and a clinical study (subsample, n=1405). Their G2 parents participated in the population-based cohorts, European Community Respiratory Heath Survey and Respiratory Health In Northern Europe, followed since the early 1990s when they were 20–44 years old, at 8–10 years intervals. Study protocols are harmonised across generations. Findings to date: Collected data include spirometry, skin prick tests, exhaled nitric oxide, anthropometrics, bioimpedance, blood pressure; questionnaire/interview data on respiratory/general/reproductive health, indoor/outdoor environment, smoking, occupation, general characteristics and lifestyle; biobanked blood, urine, gingival fluid, skin swabs; measured specific and total IgE, DNA methylation, sex hormones and oral microbiome. Research results suggest that parental environment years before conception, in particular, father's exposures such as smoking and overweight, may be of key importance for asthma and lung function, and that there is an important susceptibility window in male prepuberty. Statistical analyses developed to approach causal inference suggest that these associations may be causal. DNA methylation studies suggest a mechanism for transfer of father's exposures to offspring health and disease through impact on offspring DNA methylation. Future plans: Follow-up is planned at 5–8 years intervals, first in 2021–2023. Linkage with health registries contributes to follow-up of the cohort.